Linguistic Intersectionality (Interlinguistics) in the 21st Century: Interpreting the Intricacies and Implications of Language Contact from Bilingualism to Creole - Özyurt, Sinan (Atlas Journal, 2023)
Sociolinguistics stands as a subfield within linguistics that examines the intricate relationship between language and society. Its primary objective is to investigate the influence of internal or external societal factors on language use, considering elements such as the context of communication, characteristics of participants, and prevailing cultural norms. Communication may transpire between individuals who speak the same language or those using different languages. In cases where speakers of distinct languages find the necessity to communicate, they may engage directly as bilingual speakers, sharing language proficiency. Alternatively, they may develop a shared mode of communication. This occurrence, commonly referred to as "language contact" in academic discourse, denotes the phenomenon whereby one language exerts an impact on another. Language contact involves the transfer of linguistic features when individuals with diverse language backgrounds interact. Such interactions can yield varied outcomes, including the dominance of one language over the other, the convergence of languages, or the emergence of entirely new linguistic forms. The current study delves into numerous ramifications arising from language contact, addressing concepts like bilingualism, code-switching, borrowing, language attrition, language transfer, interference, mixed language, pidgin, creole, and interlanguage. In light of these considerations, it is striven in this review article to contribute valuable insights to the extant literature on this intricate subject.